PERFORMANCE OF GONAD MATURATION AND SPAWNED OF GROUPER BROODSTOCK CROSS BREEDING BETWEEN F-2 AND F-0 - Tri Djoko; Haryanti Haryanti; Sari Budi Moria; A Muzaki; I K Wardana (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
In fish grouper escpecially humpback grouper culture, seed and broodstock quality and availability determine the production success. Main supply of wild broodstock still dominates grouper hatchery activities, therefore, the exploitation of the wild broodstock is very high. Efforts to use the supply of cultured broodstock through selection and breeding processes will greatly determine their culture success. The purpose of this experiment was to get seeds from the cross breeding between F-2 and F-0. The research used two (2) concrete tanks with volume of 75 m3 each. Each tank was filled with 20 fishes consisting of 10 fishes of F-2 and 10 fishes of F-0. The experiment was conducted the Institute of Mariculture Research and Development, Gondol, Bali. The result showed a good gonadal development and natural spawning of cross breeding between F-2 and F-0. Total number of eggs (1.320.000) was found the highest in May in tank A, while the highest fertilized eggs of 385.000 were found in June. The SSCP analyses showed no difference in genetic characters of broodstock from cross-breeding between the female parent F-2 and F-0 male parent. Keywords: Humpback Grouper, gonad, spawned, cross breeding, larvae